Factors Supporting or Hindering the Place-based Structure of Commons in Local Productive Systems - Bellandi, Marco (REGION, 2021)
Recent results on the relationship between external economies and local public goods may be summarised as follows. Marshallian external economies are at the core of paths of development in vital local productive systems, such as Marshallian industrial districts or similar forms. They are partly external to the resources organized by single specialised firms and largely dependent on the embeddedness of the firm in the system and its various forms of division of labour. Exchanges need to integrate the contributions of the specialised producers, but all sorts of difficulties hinder them if a joint access to ‘local’ public goods does not help producers. Markets do not provide for them easily, nor top-down State planning does. Mechanisms and processes of local governance and place leadership, possibly combined with social customs and conventions, are an important support to local integration. The paper comes back to this kernel in the theories of local development, proposing an extended framework of relevant local public goods, qualified as specific public goods, club goods, and place-based common-pool resources, all sharing “commons”-like features. Factors hindering virtuous circles between external economies and specific commons are considered as well, in particular those related to different structures of interests